Comparative Study on Economics of Various Soil Conservation-cum-grassland Improvement Practices in Ravine Lands - II - Singh, Bakhshish (Indian Forester, 1971)
The effect of the various Soil Conservation-cum-Grassland improvement practices on forage production, botanical composition and soil moisture per cent was reported in an earlier paper (1). Comparative economics of those practices have been discussed in the present paper. The results indicate that the Soil and Water Conservation treatment of gully plugging and peripheral bunding combined with closure (T3) gave the highest net annual return of Rs. 107.77 per hectare. The application of fertilizers was found to be uneconomical.